Lack of supportive leadership behavior predicts suboptimal self-rated health independent of job strain after 10 years of follow-up: findings from the population-based MONICA/KORA study - Schmidt, Burkhard; Herr, Raphael (International archives of occupational and environmental health, 2018)
Emerging cross-sectional research has identified lack of supportive leadership behavior (SLB) as a risk factor for workforce health. However, prospective evidence is hitherto lacking. SLB denotes support in difficult situations, recognition and feedback on work tasks. This study aims to determine the effect of SLB on suboptimal self-rated health (SRH) after 10 years considering potential moderators such as ages, sex, occupation and job strain.
Gesehen am 02.12.2020